Gastrotricha from the Poznań Palm House—one new subgenus and three new species of freshwater Chaetonotida (Gastrotricha) - Kolicka, Małgorzata; Kisielewski, Jacek; Nesteruk, Teresa; Zawierucha, Krzysztof (Zootaxa, 2013)
Gastrotricha is a cosmopolitan phylum of aquatic and wet terrestrial invertebrates comprising about 800 described species. Gastrotrichs have never been studied in artificial habitats such as greenhouses. In this paper we present 13 species belonging to 5 genera of the family Chaetonotidae that have been found in a water body with tropical aquatic plants. Tristratachaetus subgen. nov. and Chaetonotus (Tristratachaetus subgen. nov.) rhombosquamtus sp. nov., Chaetonotus (Chaetonotus) eximius sp. nov. and Chaetonotus (Chaetonotus) pravus sp. nov. are described as a new to science. Additionally, taxonomic, biogeographic and ecological remarks for all recorded species are provided.